Review of Perinatal Deaths in a Tertiary Care Hospital of Nepal - Singh, Rajshree; Thakur, Rahul Kumar; Manandhar, Reeta; Khatri, Ratna; Thapa, Moon; Shrestha, Bikash (Nepal Journal of Obstetrics and Gynaecology, 2020)
Aims: Perinatal mortality is a public health problem especially in developing countries like Nepal. This study is an attempt to assert the perinatal mortality status for the year 2016/2017 A.D. of Shree Birendra Hospital, a tertiary hospital. This study becomes imperative to comprehend the various shortcomings in the maternal and child health care, so as to remedy them effectively. Methods: This is a hospital record-based study conducted at Shree Birendra Hospital, Kathmandu, a tertiary care facility of the Nepal Army. The record of all perinatal death from 13th April 2016 to 12th April 2017 was reviewed. Results: Out of 1051 total births, there were 12 perinatal deaths with perinatal mortality rate of 11.42 per thousand births. Perinatal death was more prevalent in the age group 20-25 (58.33%), multiparous female (60%), period of gestation between 35-40 weeks (58.34%), male gender of baby (66.67%) but equal number of deaths was seen in both vaginal delivery and emergency LSCS. According to the Wigglesworth pathophysiological classification to classify perinatal deaths, conditions specific to neonate (33.3%) constituted as a significant cause perinatal death followed by stillbirths or neonatal deaths with congenital anomalies (25%) and conditions associated with prematurity (25%). Conclusions: Neonatal sepsis contributed to the major burden of perinatal mortality. Keeping detailed medical records, screening for Group B streptococcus in the third trimester, and using clinical autopsy can further strengthen obstetric and neonatal care. Keywords: early neonatal mortality rate, perinatal mortality, stillbirth